Industri Perdagangan dan Globalisasi Maritim di Indonesia - Muhammad Nawir; Devia Ananda Umar; Nur Fitiani Rezki.HS; Wahyuddin Wahyuddin (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The era of globalization has prompted countries, including Indonesia, to reconsider their defense capabilities in the face of increasingly complex threats. Indonesia's primary focus lies in the development of the maritime sector, given its strategic geographic position between the Pacific and Indian Oceans. Maritime security is crucial for smooth trade, considering that Indonesia is the world's second-largest producer of fish. The significant potential of marine resources requires attention to maritime security. Concurrently, globalization has altered the patterns and forms of threats, especially in international trade routes such as the Malacca Strait.This research employs the method of literature study to depict Indonesia's maritime conditions, infrastructure development, and the impact of globalization on maritime trade. The government's focus on enhancing logistical efficiency and infrastructure development aims to support industrial and trade growth. However, challenges persist, particularly in optimizing the management of marine resources and improving coordination among relevant institutions. In this context, Indonesia is presented with an opportunity to become a strong maritime nation with global competitiveness, supported by an active community and a profound understanding of its maritime identity. , , .